Disciplining Christians correction and community in Augustine's letters - Ebbeler, Jennifer V. (Oxford University Press, 2012)
Disciplining Christians reconsiders several of Augustine's most well-known letter exchanges with close attention to conventional epistolary norms & practices, in an effort to identify & analyze Augustine's adaptation of the traditionally friendly letter exchange to the correction of perceived error in the Christian community
Includes bibliographical references and index
Keywords: Augustine / Saint, Bishop of Hippo / Correspondence; Augustinus, Aurelius -- Heiliger -- 354-430 -- Epistulae; Geschichte; Discipling (Christianity) / History / To 1500; Disziplinierung